Unilateral and unilocular adnexal cysts in postmenopausal women: a diagnostic and therapeutic problem - Fuchs, Tomasz; Grobelak, Krzysztof; Pomorski, Michał; Woytoń, Robert; Tomiałowicz, Marek; Zimmer, Mariusz (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : Unilateral and unilocular ovarian cysts are an important problem in contemporary gynecology. Due to the fact that 10% of ovarian tumors are malignant, it is important to answer the question if the ovarian cyst detected in ultrasound examination requires surgical procedures or just further follow-up. The aim of this study was to estimate the rate of malignancy in adnexal lesions described during transvaginal scan as a unilateral and unilocular cyst in postmenopausal women. Material and methods: Ninty postmenopausal women, aged 50 to 81, with presence of adnexal masses were examined using transvaginal ultrasound in gray scale and color Doppler, and pulsed Doppler as well, and then treated surgically in the Department of Gynecology and Obstetrics, Medical University in Wroclaw. Each lesion was tested histologically. Results: In the postoperative pathological examination, 89 (98.89%) lesions were characterized as benign. The most common diagnosis was cystis serosa ovarii (65.6%). Only one lesion (1.1%) turned out to be tumor of borderline malignancy: cystadenofibroma papillare serosum ovarii casus limitans. Conclusions : The rate of malignancy in adnexal lesions described as unilateral and unilocular cysts diagnosed by transvaginal ultrasound in postmenopausal women is low. Most adnexal tumors detected in ultrasound scan turned out in the pathological examination to be benign. Non-surgical procedures in cases of unilateral and unilocular cysts, especially smaller than 50 mm, in postmenopausal women seem to be safe procedures recommended especially for women with other chronic diseases.